Novel forms of forgetting in temporal lobe epilepsy. - Zeman, A; Butler, C; Muhlert, N; Milton, F (2013)
Transient Epileptic Amnesia (TEA) is a recently defined subtype of temporal lobe epilepsy, principally affecting people in middle age with a male predominance. Its key manifestation is the occurrence of recurring episodes of transient amnesia, usually lasting less than an hour and often occurring on waking. One-third of patients have exclusively amnestic attacks, while in two-thirds, at least some attacks are accompanied by other manifestations of epilepsy, especially olfactory hallucinations. Several lines of evidence point to a seizure focus in the medial temporal lobes. Transient Epileptic Amnesia is accompanied by a striking loss of autobiographical memories in two-thirds of sufferers, accelerated loss of memories which had been acquired successfully in around one half, and topographical amnesia in around one-third. This paper reviews the findings of the TIME project (The Impairment of Memory in Epilepsy - http://sites.pcmd.ac.uk/time/tea.php) in relation to TEA, accelerated long-term forgetting, and remote memory impairment.